What is the benefit of inconsistent opioid agonist treatment in patients with prescription opioid use disorder? - R. Weiss; M. L. Griffin (European Psychiatry, 2023)
Introduction Studies consistently show that patients with prescription opioid use disorder (OUD) respond to buprenorphine treatment. Few studies have followed these patients in the long-term. Our longitudinal research has shown opioid abstinence to be associated most strongly with opioid agonist/partial agonist treatment. We also found that many patients used agonist treatment inconsistently; questions remain about the benefits of intermittent opioid agonist treatment. Objectives We examined patients during the 3.5 years following their entry into a 3-month trial of treatment for prescription OUD. The current analysis compared opioid use outcomes among patients who reported receipt of agonist treatment consistently, inconsistently, or never. Methods This secondary analysis (N=309) of a U.S. multi-site randomized controlled trial of treatment for prescription OUD assessed variability in receiving opioid agonist treatment during the 3.5-year follow-up period, and the association between agonist treatment and opioid abstinence. Assessments were collected at months 18, 30, and 42 following treatment entry; patients were asked if they were currently taking agonist treatment and whether they had used other opioids in the previous month. Patients with only one follow-up assessment (n=29) were excluded from this analysis. Results Most patients reported current opioid abstinence on at least one follow-up visit: 38% were always abstinent, 41% sometimes, and 21% never. Twenty-three percent always reported currently using agonist treatment, 26% sometimes, and 51% never. Patients consistently reporting agonist use were most likely to always be opioid-abstinent in the past month (69%), with 25% sometimes and 6% never abstinent. Patients who never reported agonist use were equally likely to be abstinent never (32%), sometimes (35%), and always (32%). Patients who sometimes reported receiving agonists were most likely to report abstinence sometimes (65%); 14% never reported abstinence, and 21% always did. Those consistently receiving agonist treatment were more likely to always be opioid-abstinent (69%) than those sometimes (21%) or never (32%) receiving agonists. Those never receiving agonist treatment were more likely to never report opioid abstinence (32%) than were those sometimes (14%) or always (6%) receiving agonists. Interestingly, those who sometimes received agonists were more likely to be abstinent than those who never received agonists: those who sometimes received agonists were more likely to be abstinent sometimes than those who never received agonists (65% vs. 35%) and less likely to never be abstinent than were those who never received agonists (14% vs. 32%). Conclusions Receiving opioid agonist treatment has been shown to be associated with opioid abstinence during long-term follow-up. This study shows that even those who only inconsistently receive agonists are also likely to benefit. Disclosure of Interest R. Weiss Consultant of: Alkermes, M. Griffin: None Declared